1998
DOI: 10.1507/endocrj.45.165
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Free Fatty Acids Decrease Splanchnic Glucose Uptake in Patients with Non-Insulin-Dependent Diabetes Mellitus.

Abstract: Abstract. It has been proposed that high plasma free fatty acid (FFA) levels observed in patients with non-insulin dependent diabetes mellitus (NIDDM) contribute to the development of their insulin resistance. We examined patients with NIDDM to find whether maintaining plasma FFA levels in the fasting range with a euglycemic hyperinsulinemic clamp combined with an oral glucose load (clamp OGL) would affect insulin-mediated peripheral glucose uptake (PGU) and splanchnic glucose uptake (SGU). Nine NIDDM subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The effect of FFAs on splanchnic glucose uptake has been less clear, likely due in large part to differences in the methods used in the previous studies. Tomita et al (21) used the hyperinsulinemic clamp technique to demonstrate that elevated FFAs decreased the glucose infusion rate required to maintain euglycemia after glucose ingestion. Rigalleau et al (20) reported that the exogenous glucose appearance rate after glucose ingestion was increased during lipid infusion, whereas Kruszynska et al (23) reported no change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of FFAs on splanchnic glucose uptake has been less clear, likely due in large part to differences in the methods used in the previous studies. Tomita et al (21) used the hyperinsulinemic clamp technique to demonstrate that elevated FFAs decreased the glucose infusion rate required to maintain euglycemia after glucose ingestion. Rigalleau et al (20) reported that the exogenous glucose appearance rate after glucose ingestion was increased during lipid infusion, whereas Kruszynska et al (23) reported no change.…”
Section: Discussionmentioning
confidence: 99%
“…People with type 2 diabetes commonly have elevated FFA and glycerol concentrations (1,5,6). Although it is well established that FFAs can blunt the response of muscle to insulin (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), elevated FFAs have been reported to increase (20), decrease (21), or have no effect (22,23) on initial splanchnic glucose extraction. The lack of concordance between these studies may be due in part to the fact that none of these studies directly measured splanchnic glucose uptake.…”
mentioning
confidence: 99%
“…Because elevated plasma FFA levels stimulate gluconeogenesis (33) and impair the suppression of hepatic glucose production in vivo (34), this could explain, in part, the improvement in oral glucose tolerance after pioglitazone treatment. Elevated plasma FFA levels also have been shown to decrease splanchnic (hepatic) glucose uptake in type 2 diabetic individuals (35). It is of interest to speculate that the decrease in plasma FFA concentration is associated with mobilization of lipid from muscle, leading to enhanced muscle sensitivity to insulin (36).…”
Section: Regression Analysesmentioning
confidence: 99%
“…Tomita et al [53] reported that the exogenous glucose infusion rate required after ingestion of glucose to maintain euglycemia during a hyperinsulinemic clamp was lower in type 2 diabetic subjects during a lipid emulsion infusion than during a saline infusion. Bajaj et al [54] reached the same conclusion using essentially the same experimental approach.…”
Section: Effects Of Experimental Interventions That Raise or Lower Ffmentioning
confidence: 99%